Implementasi Aplikasi Data Center Infrastructure Management (Dcim) Berdasarkan Arsitektur Microservices Menggunakan Kubernetes Studi Kasus Pt. Pelayaran Nasional Indonesia (Pelni): (Dcim) - Elizabeth Margaretha Sitorus, Bintang; Iqbal, Muhammad; Mahendra Putra, Chadra (eProceedings of Applied Science, 2024)
In this digital age, companiesare facing pressure to upgrade theirIT infrastructure to manage data more effectively, securely,and scalable. The data infrastructure iskey to maintaining smooth services and operations,especially for large enterprises with complex and extensive data centerscomplex and extensive data centers. PT Pelayaran Nasional Indonesia(PELNI), as a leading company in the shipping industry, is also facing similar challenges in itsshipping industry, also faces similar challenges inmanaging their data center infrastructure. This researchutilizing microservices architecture and containercontainer orchestration platform such as Kubernetes, PT. Pelayaran Nasional Indonesia (PELNI)National Indonesia (PELNI) has upgraded their data center management system to a higher level.management system to a higher level.To manage the data center infrastructure, PT.Pelayaran Nasional Indonesia (PELNI) requires an advanced, integratedadvanced and integrated monitoring system to monitordata collection and infrastructure performance in real-time.Therefore, the integration of Data Center InfrastructureManagement (DCIM) application integration using Kubernetes ArchitectureKubernetes architecture is a must for PT Pelayaran Nasional Indonesia (PELNI).National Indonesia (PELNI). It is expected that thisthis final project can plan, implement, andmonitor infrastructure using Kubernetes forData Center Infrastructure Management (DCIM) application atPT Pelayaran Nasional Indonesia (PELNI). These steps not only improveoperational efficiency, but also allows PT. Pelni to be able toaddress the needs and challenges of better data center managementmanagement needs and challenges. By implementing Kubernetes, PT.Pelayaran Nasional Indonesia (PELNI) canimprove network documentation and management,and strengthen the security of data infrastructure servicesDCIM services.Keywords: kubernetes, DCIM, architecturemicroservices architecture, netbox